Structural aspects and ecophysiology of anther opening in Allium triquetrum - Carrizo Garcia, Carolina (2006)
Background and Aims Tissue desiccation is considered to be involved in anther opening, and it is agreed that environmental humidity affects its timing. Different sources of evidence suggest that the later steps of the process (i.e. stomium opening and outward wall bending) are regulated in different ways. Anther opening was studied in Allium triquetrum under four regimes of relative humidity (RH) to analyse the effect of this parameter and to speculate about its possible regulation. Methods Anther histology was studied in cross-sections under a microscope. The times of visible anther opening and complete outward wall bending were recorded separately for each level of RH. Frequency distributions were plotted to express anther behaviour. Key Results When a longitudinal stomium breaks the anther remains closed due to adherence of walls on each side of the stomium. Anther opening occurs when the adhering walls subsequently separate. Later, the walls shrink laterally and bend outward. The anthers of the inner whorl opened during the morning of the first day of anthesis, while those of the outer whorl opened during the afternoon. Low RH (20 %) did not cause any evident acceleration of anther opening, but it did cause delay and inhibition of the opening of some anthers in the outer whorl. High RH (55 and 98 %) caused different degrees of delay and also inhibition of anther opening, but most anthers opened within the expected range of time. The time taken for outward wall bending was shortened at 20 % RH. Anther wall outward bending was inhibited at 55 % and 98 % RH. Conclusions Anther opening occurred at a specific moment of anther development, separated in time from stomium breakage, and seemed related to dehydration caused by reabsorption of water by contiguous tissues. Outward bending of the wall was facilitated by evaporation. Anther opening and anther wall outward bending seemed to be regulated differently in relation to water control.